2020
DOI: 10.3390/app10165463
|View full text |Cite
|
Sign up to set email alerts
|

A New Vector-Based Signal Processing Method of Four-Sensor Probe for Measuring Local Gas–Liquid Two-Phase Flow Parameters Together with Its Assessment against One Bubbly Flow

Abstract: A multiphase flow measurement technique plays a critical role in the studies of heat and mass transfer characteristics and mechanism of the gas–liquid two-phase, the practical measurement of the gas–liquid flow and the improvement of multiphase theoretical models. The four-sensor electrical probe as an emerging measurement method has been proved to be able to get the local flow parameters of multi-dimensional two-phase flow. However, few studies have been reported using the four-sensor probe to obtain the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…It has also been used to measure the size and velocity of the dispersed phase droplets/bubbles on a smaller scale. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Optical fiber probe technology was originally utilized in gas-liquid two-phase flow systems, and now is used extensively in both gas-liquid and liquid-liquid twophase systems. Optical fiber probes are classified as mono, double, triple, four, and five optical fibers based on the number of optical fibers in the sensor probe.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has also been used to measure the size and velocity of the dispersed phase droplets/bubbles on a smaller scale. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Optical fiber probe technology was originally utilized in gas-liquid two-phase flow systems, and now is used extensively in both gas-liquid and liquid-liquid twophase systems. Optical fiber probes are classified as mono, double, triple, four, and five optical fibers based on the number of optical fibers in the sensor probe.…”
Section: Introductionmentioning
confidence: 99%
“…The four-optical fiber probe method is more suitable for measuring three-dimensional velocity and size of the droplet/bubble. 23,24 Mishra 25 and Lucas 26 measured the velocity vector of a spherical droplet and nonspherical bubble by an orthogonal arrangement. It was indicated that the geometric arrangement of four probes has an impact on the measurement error; the triangle arrangement generates less error than the orthogonal arrangement.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bak et al (2020) proposed a semi-theoretical correlation developed from a steady-state bubble number density transport equation for predicting the distribution of local bubble size. To obtain physical mechanism governing the air-water interaction, a new method to determine the bubble velocity magnitude was proposed (Qu et al, 2020). Giorgio et al (2016) provided an experimental method to observe the motion of air bubbles by using a light-field camera, and then analyzed the flow properties and distribution of the air bubbles.…”
mentioning
confidence: 99%